THE RELATIONSHIP BETWEEN SELF-ESTEEM AND PSYCHOLOGICAL WELL-BEING WITH LONELINESS AMONG COLLEGE STUDENTS IN SIDOARJO - Indriyani, Nur Afidah; Zaki Nur Fahmawati (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Students are individuals who are in the early adulthood phase who are in the age range of 18 ± 40 years. In addition to individuals in the early adulthood phase, students are also susceptible to loneliness. This study aims to determine the relationship between self-esteem and psychological well-being with loneliness in students in Sidoarjo. Method: The population in this study was 23,039 students with a research sample using cluster sampling using the Isaac & Michael formula with a 5% error rate involving 342 students. Results: The results showed that there was a relationship between self-esteem and psychological well-being with loneliness in students in Sidoarjo with a Pearson's correlation test value of r = -0.468 for self-esteem and Pearson's correlation r = -0.419 for psychological well-being, p < .001. This indicates a significant negative relationship between self-esteem, psychological well-being, and loneliness among students in Sidoarjo. Novelty: This suggests that higher self-esteem and psychological well-being correlate with lower loneliness levels, and vice versa.